FRP composites for flexural strengthening of concrete structures theory, testing, design - Kotynia, Renata (Wydawnictwo Politechniki Łódzkiej, 2019)
The purpose of this book is to provide structural and mechanical engineers with simplified and advanced model for flexural strengthening of reinforced concrete members with externally bonded (called in the last nomenclature EB) FRP reinforcement. The review of existing bond models is to explain phenome-non of bond losing between FRP and concrete. The detailed analysis of variable parameters shows complexity this problem.
Cover design: Krotowski, Tomasz
Text setting: Filipczak, Jacek
Keywords: FRP composites; FRP materials; flexural strengthening; bond strength models; nonlinear finite element models